Geomorphology of the Upper Basin of Tohma Stream (West of Kangal) - Sunkar, Murat; Ozdemir, M. Ali; Tonbul, Saadettin (Istanbul Univ, Fac Letters, Dept Geography, 2008)
This study focus on geomorphological properties of Tohma Stream's Upper Basin and its' morphological development. Study area consist of west half of Kangal Basin which constitutes eastern part of Uzunyayla Plateau. Kangal Basin on Late Miocene-Pliocene which are surrounded by highland, are a structural plateau area. Because of the fact that the highland in North and South has been limited by the thrust and reverse faults, the research area is the intermontane basin. This types of basin which had been formed in neo orogenical zones, are called Piggy-back basin in geology. Highland, plateau and valleys are main morphological units in the research area in which its height is approximately 1650 m. Left lateral faults in the strike of northeast-southwest and right lateral faults in the strike of northwest-southeast which cut the left lateral fault, vertically, developed as secondary faults in the north and south of basin. Offset ridge and valley, fault scarps, sag-pond, triangular facets, and big mass movements have been seen throughout fault zones. Geomorphological units can be seen in curled, faulty, horizontal and monoclinal structure at the Basin which is important in terms of morphological and tectonic. Typical karstic units developed on limestones based on Mesozoic, Miocene and Pliocene. The Basin which was the sedimentation area throughout Late Miocene-Pliocene had been bounded to the external drainage by dried up lakes in Quaternary. Rivers which sink deeply into their beds on the basin gangue, epirogeneticly, had constituted important gorges.
Keywords: Uzunyayla Plateau; Tohma Stream; Structural Plateau; Intermontane basin